Flood facilitates cross‐ecosystem trophic subsidies to marine animals - Paul J. McInerney; Christopher M. Bice; Darren P. Giling; Matt Gibbs; Luke Mosley; Mark Doubell; Hugo Bastos de Oliveira; Ian Moody; Brenton P. Zampatti (Limnology and Oceanography, 2026)
Trophic subsidies are resources that cross ecosystem boundaries, influencing the structure and function of recipient food webs. Widespread regulation of rivers for human consumptive use has profoundly altered natural flow regimes, decoupling donor‐recipient dynamics between freshwater and marine ecosystems. We explored trophic subsidies to the Southern Indian Ocean from a highly regulated river during a 1 in 66‐year flood by comparing δ 15 N, δ 13 C and δ 34 S values of three marine trophic guilds sampled across the flood plume and at geographically isolated reference locations. Secondary and tertiary consumers collected within the flood plume were δ 15 N enriched compared to reference animals and isotopic niche overlap declined across higher trophic levels (24% and 6% respectively). For both yellow‐eye mullet ( Aldrichetta forsterii —a secondary consumer) and Australasian snapper ( Chrysophrys auratus —a tertiary consumer), there was no overlap in isotopic niche between flood plume and reference animals. Terrestrial contributions to marine animal biomass in the flood plume varied by trophic level and subsidies were highest among secondary consumers (35% compared to 22% for reference animals). Terrestrial contributions to tertiary consumers (29%) did not significantly diverge from reference estimates (21%), as evidenced by overlapping 95% credible intervals. This modest difference likely stems from a temporal mismatch between the flood peak and slower isotopic turnover rates among large predators. Our results emphasize that dietary integration reflected in secondary consumers provided the most reliable subsidy estimates due to exposure duration and representative body mass. Here, we demonstrate significant trophic subsidies resulting from the temporary re‐establishment of river‐marine coupling in a highly regulated river. Our findings provide quantitative empirical support for trophic ecological theory and underpin the importance of managing freshwater‐marine linkages in the face of anthropogenic pressures.

The impact of a mega-flood event on the water quality of the southern Murray-Darling Basin, Australia - Dilanka Athukoralalage; Justin D. Brookes; Richard W. McDowell; Luke M. Mosley (Journal of Hydrology, 2026)

Eucalypt Leaf Litter and a Drying-Rewetting Cycle Shape Wetland Soil-Water Nutrient Dynamics: A Laboratory Microcosm Study - Rui Yan; Luke Mosley; Petra Marschner (Wetlands, 2026)
This study used laboratory column microcosms with River Murray (Australia) wetland soils and water to examine how drying-rewetting (DRW) and river red gum ( Eucalyptus camaldulensis ) litter inputs interactively affect nitrogen (N), phosphorus (P), and carbon dynamics across soil, pore water, and overlying water. We quantified N and P species and dissolved organic carbon (DOC) under two water regimes (constant submergence versus DRW) with and without litter addition to resolve cross-compartment responses at the aquatic-terrestrial interface. DRW enhanced net inorganic-N mobilization, resulting in pronounced post-rewetting pulses in pore-water and overlying-water N (especially NH 4 + ) compared to constant submergence, with concentrations gradually converging during prolonged inundation. Conversely, total P and inorganic P (P i ) were higher under constant submergence, consistent with sustained reducing conditions promoting P release in solution. Although litter inputs did not substantially alter total nutrient levels in overlying water, they shifted pore-water chemistry by increasing the proportion of inorganic P and strongly elevating DOC. Following rewetting, DOC increased sharply in litter-amended treatments, ~ 2.9-fold in overlying water and ~ 16.8-fold in pore water, compared with no-litter treatments. Litter addition also reduced nitrate availability in soil and pore water during resubmergence, consistent with stronger microbial N retention and/or NO 3 − consumption under rapidly re-established reducing microsites after rewetting. Overall, DRW and litter inputs interact to amplify short-lived C and N pulses while modifying P speciation, with implications for predicting nutrient availability and water-quality risk in wetlands experiencing increasingly variable hydrological regimes.

Microbial ecology in hypersaline coastal lagoons: A model for climate-induced coastal salinisation and eutrophication - Christopher Keneally; Virginie Gaget; Daniel Chilton; Stephen P. Kidd; Luke Mosley; David T. Welsh; Yongqiang Zhou; Lei Zhou; Justin Brookes (Earth-Science Reviews, 2025)

Assessing wheat responses to soil acidification and liming using hyperspectral imaging - Ruby Hume; Petra Marschner; Sean Mason; Rhiannon K. Schilling; Huajian Liu; Nathaniel Jewell; Christoper J. Brien; Luke M. Mosley (Plant and Soil, 2025)

Understanding sediment nutrient cycling in a hypersaline coastal lagoon using hydrogel-based passive sampling techniques - Jianyin Huang; Orlando Lam-Gordillo; Luke M. Mosley; Christopher Keneally; Justin Brookes; David T. Welsh (Marine Pollution Bulletin, 2025)

Isotopically resolved fate and processes of nitrogen in a constructed wetland treating domestic effluent - Danielle J. Allen; Mark Farrell; Wei Wen Wong; Jianyin Huang; Luke M. Mosley (Science of The Total Environment, 2025)

Vertical Accretion Trends in Australian Tidal Wetlands - Neil Saintilan; Yujie Sun; Catherine E. Lovelock; Kerrylee Rogers; Madeline Goddard; Lindsay B. Hutley; Jeffrey Kelleway; Luke Mosley; Sabine Dittmann; Nicole Cormier; Kirti K. Lal; Alice Jones (Estuaries and Coasts, 2024)
Australian tidal wetlands differ in important respects to better studied northern hemisphere systems, an artefact stable to falling sea levels over millennia. A network of Surface Elevation Table-Marker Horizon (SET-MH) monitoring stations has been established across the continent to assess accretionary and elevation responses to sea-level rise. This network currently consists of 289 SET-MH installations across all mainland Australian coastal states and territories. SET-MH installations are mostly in mangrove forests but also cover a range of tidal marsh and supratidal forest ecosystems. Mangroves were found to have higher rates of accretion and elevation gain than all the other categories of tidal wetland, a result attributable to their lower position within the tidal frame (promoting higher rates of accretion) higher biomass (with potentially higher rates of root growth), and lower rates of organic decomposition. While Australian tidal marshes in general show an increase in elevation over time, in 80% of locations, this was lower than the rate of sea-level rise. High rates of accretion did not translate into high rates of elevation gain, because the rate of subsidence in the shallow substrate increased with higher accretion rates ( r 2 = 0.87). The Australian SET-MH network, already in many locations spanning two decades of measurement, provides an important benchmark against which to assess wetland responses to accelerating sea-level rise in the decades ahead.

Organic matter accumulation drives methylotrophic methanogenesis and microbial ecology in a hypersaline coastal lagoon - Christopher Keneally; Matilda Southgate; Daniel Chilton; Virginie Gaget; David T. Welsh; Luke Mosley; Dirk V. Erler; Stephen P. Kidd; Justin Brookes (Limnology and Oceanography, 2024)
Hypersalinity is common in coastal wetlands throughout warm, tropical, and arid regions. Climate‐induced changes in rainfall, sea level, and anthropogenic modification to basins and coastlines are likely to further increase salinization in these ecosystems. Yet, carbon cycling in hypersaline coastal wetlands is not well understood, and poorly constrained in climate models. In the Coorong, a eutrophic, hypersaline coastal lagoon, recognized as internationally important under the Ramsar convention, organic matter rapidly accumulates in deeper areas of the lagoon, through the settling of fine detrital particles, phytoplankton and suspended sediments. During initial surveys, elevated surface water methane (CH 4 ) concentrations were observed above these fine depositional sediments. To identify the drivers of CH 4 production, organic matter and sediment characteristics were assessed in surface sediments. Genetic markers (i.e., 16rDNA and the mcrA functional gene) were used to characterize microbial communities. With multiple lines of evidence, this study identifies organic matter, methanogen abundance, and salinity as important drivers of CH 4 production, which is concentrated in depositional zones. Archaea were also more abundant in depositional zones, including methylotrophic methanogens: Methanofastidiosales, Methanomasiliicoccales, Methermicoccaceae , and Methanococcoides . These methanogens were highly correlated to CH 4 in porewater, suggesting an influence of methylotrophic methanogenesis. To investigate further, metabolic genes were predicted from 16S rRNA with PICRUSt2. This represents the first effort to analyze CH 4 dynamics in the Coorong, underscoring the need to integrate these unique ecosystems into global climate models to enhance our understanding of greenhouse gas dynamics and emissions in a changing climate.

Using mid-infrared spectroscopy as a tool to monitor responses of acidic soil properties to liming: case study from a dryland agricultural soil trial site in South Australia - Ruby Hume; Petra Marschner; Sean Mason; Rhiannon K. Schilling; Luke M. Mosley (Precision Agriculture, 2024)
Soil acidification is an issue for agriculture that requires effective management, typically in the form of lime (calcium carbonate, CaCO 3 ), application. Mid infrared (MIR) spectroscopy methods offer an alternative to conventional laboratory methods, that may enable cost-effective and improved measurement of soil acidity and responses to liming, including detection of small–scale heterogeneity through the profile. Properties of an acidic soil following lime application were measured using both MIR spectroscopy with Partial Least Squares Regression (MIR-PLSR) and laboratory measurements to (a) compare the ability of each method to detect lime treatment effects on acidic soil, and (b) assess effects of the different treatments on selected soil properties. Soil properties including soil pH (in H 2 O and CaCl 2 ), Aluminium (Al, exchangeable and extractable), cation exchange capacity (CEC) and organic carbon (OC) were measured at a single field trial receiving lime treatments differing in rate, source and incorporation. Model performance of MIR-PLSR prediction of the soil properties ranged from R 2 = 0.582, RMSE = 2.023, RPIQ = 2.921 for Al (extractable) to R 2 = 0.881, RMSE = 0.192, RPIQ = 5.729 for OC. MIR-PLSR predictions for pH (in H 2 O and CaCl 2 ) were R 2 = 0.739, RMSE = 0.287, RPIQ = 2.230 and R 2 = 0.788, RMSE = 0.311, RPIQ = 1.897 respectively, and could detect a similar treatment effect compared to laboratory measurements. Treatment effects were not detected for MIR-PLSR-predicted values of CEC and both exchangeable and extractable Al. Findings support MIR-PLSR as a method of measuring soil pH to monitor effects of liming treatments on acidic soil to help inform precision agricultural management strategies, but suggests that some nuance and important information about treatment effects of lime on CEC and Al may be lost. Improvements to prediction model performance should be made to realise the full potential of this approach.

Impact of hydrological drought occurrence, duration, and severity on Murray-Darling basin water quality - Dilanka Athukoralalage; Justin Brookes; Rich W. McDowell; Luke M. Mosley (Water Research, 2024)

Novel insight into ammonium, phosphate, and iron(II) dynamics in the sediment porewater of a constructed wetland under artificial aeration through the diffusive equilibrium in thin films technique - Danielle J. Allen; Jianyin Huang; Mark Farrell; Luke M. Mosley (Environmental Research, 2023)

Measurement of lime movement and dissolution in acidic soils using mid-infrared spectroscopy - Ruby Hume; Petra Marschner; Sean Mason; Rhiannon K. Schilling; Brian Hughes; Luke M. Mosley (Soil and Tillage Research, 2023)

Mapping soil corrosivity in an Australian arid environment and comparing corrosion rates of exclusion fence netting with different zinc coatings - Andrea D. Stiglingh; Luke M. Mosley; Ronald J. Smernik; Robert W. Fitzpatrick (Geoderma Regional, 2023)

Controls on sulfide accumulation in coastal soils during simulated sea level rise - Emily Leyden; Juraj Farkaš; John Hutson; Luke M. Mosley (Geochimica et Cosmochimica Acta, 2023)

Artificial aeration of an overloaded constructed wetland improves hypoxia but does not ameliorate high nitrogen loads - Danielle J. Allen; Mark Farrell; Jianyin Huang; Simon Plush; Luke M. Mosley (Journal of Environmental Management, 2023)

Ensuring planetary survival: the centrality of organic carbon in balancing the multifunctional nature of soils - Peter M. Kopittke; Asmeret Asefaw Berhe; Yolima Carrillo; Timothy R. Cavagnaro; Deli Chen; Qing-Lin Chen; Mercedes Román Dobarco; Feike A. Dijkstra; Damien J. Field; Michael J. Grundy; Ji-Zheng He; Frances C. Hoyle; et al. (Critical Reviews in Environmental Science and Technology, 2022)

Combined Effects of Hydrological Drought and Reduced Food Availability on the Decline of the Little Penguins in South Australia - Diane Colombelli-Négrel; Darfiana Nur; Hannah C. C. Auricht; Kenneth D. Clarke; Luke M. Mosley; Peter Dann (Frontiers in Marine Science, 2022)
Droughts in many regions of the world are increasing in frequency and severity which, coupled with effects from anthropogenic water extraction and diversion, are reducing river discharges. Yet to date, few studies have investigated the impacts of hydrological droughts (i.e., reduced river outflows to the ocean) on seabirds. Here, we examined the consequences of the “Millennium Drought” on the local decline of an iconic Australian seabird, the little penguin ( Eudyptula minor ). We analysed monthly and annual penguin numbers in relation to river outflow, rainfall, the characteristics of the coastal waters (sea surface temperatures and chlorophyll- a concentrations), and local abundance of key predators and prey species. We found a negative association between monthly penguin numbers and both sea surface temperatures and river outflow. Annual penguin numbers were positively associated with southern garfish numbers (our local indicator of food availability) but negatively associated with annual chlorophyll- a concentrations. Our findings emphasizing the need for further research into the effect of hydrological droughts on seabird populations and for improved river management that account for potential downstream impacts on the coastal environment receiving freshwater from rivers.

Correction to: Phosphorus speciation and release from different plant litters on a River Murray (Australia) floodplain - Xihe Zhang; Ronald Smernik; Ashlea Doolette; Samantha Walters; Luke M. Mosley (Plant and Soil, 2022)

Application of visible near-infrared absorbance spectroscopy for the determination of Soil pH and liming requirements for broad-acre agriculture - Bethany Sleep; Sean Mason; Les Janik; Luke Mosley (Precision Agriculture, 2022)

Phosphorus speciation and release from different plant litters on a River Murray (Australia) floodplain - Xihe Zhang; Ronald Smernik; Ashlea Doolette; Samantha Walters; Luke M. Mosley (Plant and Soil, 2022)

Phosphorus Pools in Acid Sulfate Soil Are Influenced by pH, Water Content, and Addition of Organic Matter - Sonia Mayakaduwage; Luke M. Mosley; Petra Marschner (Journal of Soil Science and Plant Nutrition, 2021)

Effect of Short-term Irrigation of Wastewater on Wheat Growth and Nitrogen and Phosphorus in Soil - Thi Huong Xuan Le; Luke Mosley; Dinh Thi Nguyen; Petra Marschner (Journal of Soil Science and Plant Nutrition, 2020)

Phosphorus pools in sulfuric acid sulfate soils: influence of water content, pH increase and P addition - Sonia Mayakaduwage; Md Alamgir; Luke Mosley; Petra Marschner (Journal of Soils and Sediments, 2020)

Nitrogen and phosphorus removal from wastewater by sand with wheat straw - Thi Huong Xuan Le; Luke Mosley; Petra Marschner (Environmental Science and Pollution Research, 2019)

From Mountain Ranges to Sweeping Plains, in Droughts and Flooding Rains; River Murray Water Quality over the Last Four Decades - Tapas K. Biswas; Luke M. Mosley (Water Resources Management, 2019)

Organic materials retain high proportion of protons, iron and aluminium from acid sulphate soil drainage water with little subsequent release - Tan Dang; Luke M. Mosley; Rob Fitzpatrick; Petra Marschner (Environmental Science and Pollution Research, 2016)

Type of organic carbon amendment influences pH changes in acid sulfate soils in flooded and dry conditions - Nilmini Jayalath; Rob W. Fitzpatrick; Luke Mosley; Petra Marschner (Journal of Soils and Sediments, 2016)

Organic Materials Differ in Ability to Remove Protons, Iron and Aluminium from Acid Sulfate Soil Drainage Water - Tan Dang; Luke M. Mosley; Rob Fitzpatrick; Petra Marschner (Water, Air, & Soil Pollution, 2015)

The capacity of biochar made from common reeds to neutralise pH and remove dissolved metals in acid drainage - Luke M. Mosley; Philip Willson; Benjamin Hamilton; Greg Butler; Russell Seaman (Environmental Science and Pollution Research, 2015)

Monitoring and assessment of surface water acidification following rewetting of oxidised acid sulfate soils - Luke M. Mosley; Benjamin Zammit; Ann-Marie Jolley; Liz Barnett; Rob Fitzpatrick (Environmental Monitoring and Assessment, 2014)

Options for Managing Hypoxic Blackwater in River Systems: Case Studies and Framework - Kerry L. Whitworth; Janice L. Kerr; Luke M. Mosley; John Conallin; Lorraine Hardwick; Darren S. Baldwin (Environmental Management, 2013)

The Impact of Extreme Low Flows on the Water Quality of the Lower Murray River and Lakes (South Australia) - Luke M. Mosley; Benjamin Zammit; Emily Leyden; Theresa M. Heneker; Matthew R. Hipsey; Dominic Skinner; Kane T. Aldridge (Water Resources Management, 2012)

Pollutant Loads Returned to the Lower Murray River from Flood-Irrigated Agriculture - Luke M. Mosley; Nigel Fleming (Water, Air, & Soil Pollution, 2010)

Hydrogen peroxide concentrations in relation to optical properties in a fiord (Doubtful Sound, New Zealand) - Barrie M. Peake; Luke M. Mosley (New Zealand Journal of Marine and Freshwater Research, 2004)
Hydrogen peroxide concentrations are reported for the first time in the surface low salinity layer (LSL) and underlying saline layer (SL) of a fiord. Measurements were made in Deep Cove and Hall Arm in Doubtful Sound, New Zealand under contrasting climatic conditions in early summer (October; wet, windy, and dull: November; dry, still, and sunny). Steady state peroxide concentrations in the range 100–400 nM rapidly declined with depth in the LSL and across the LSL/SL interface. Spectral measurements of absorption coefficients and downwelling irradiance indicated this is largely because of high levels of chromophoric dissolved organic matter (CDOM) in the LSL filtering out the UV component ( M) .

Partitioning of metals (Fe, Pb, Cu, Zn) in urban run‐off from the Kaikorai Valley, Dunedin, New Zealand - Luke M. Mosley; Barrie M. Peake (New Zealand Journal of Marine and Freshwater Research, 2001)
Urban run‐off from a catchment in Dunedin, New Zealand was sampled and chemically characterised (iron (Fe), lead (Pb), copper (Cu), zinc (Zn) in total and 0.4 μm) and their concentrations increased significantly at the beginning of storm run‐off. In contrast, the majority of Cu and Zn was found in the 0.4 μm fraction. The results indicate that Cu and Zn may be more bio‐available, and more difficult to remove by storm‐water treatment, than Pb. The pH level and the concentration of major ions (Ca +2 , Na + , Mg +2 , K + ), dissolved reactive phosphorus, and nitrate generally decreased during storm flows as a result of dilution by rainwater. Concentrations of total N and P often increased during the initial period of storm run‐off, which was likely because of wash‐off of particulate plant material.